Polymerizable wedge-shaped ionic liquid crystals for fabrication of ion-conducting membranes: Impact of the counterion on the phase structure and conductivity. (August 2016) - Hernandez Rueda, Jaime J.; Zhang, Heng; Rosenthal, Martin; Möller, Martin; Zhu, Xiaomin; Ivanov, Dimitri A.
Graphical abstract: Highlights: Fabrication of ion-selective polymer membranes by self-assembly of wedge-shaped mesogens is described. The supramolecular structure of the wedges can be arrested by photo-polymerization. The influence of the counter ion on the structure of the mesophases and electrical conductivity is discussed. Abstract: In this manuscript, we report on the phase behavior of a novel family of ionic liquid crystals based on wedge-shaped amphiphilic mesogens of benzene sulfonates with different counterions (Li, Na, K and Cs) and polymerizable acrylic groups in the alkyl chain periphery. The phase diagrams of these compounds were explored with differential scanning calorimetry, polarized optical microscopy and temperature-dependent small-angle X-ray scattering. Lamellar and columnar liquid-crystalline phases were identified. Ionic conductivity was measured by impedance spectroscopy at different relative humidities. The influence of the counterion on the mesostructure and electrical conductivity is further discussed. Finally, it is demonstrated how photopolymerization can be employed to arrest the different supramolecular structures and transform the low-molecular-weight nanostructured liquid into self-standing ion conducting polymer membranes.